2021
DOI: 10.1093/mnras/stab498
|View full text |Cite
|
Sign up to set email alerts
|

Radio and optical observations of the possible AE Aqr twin, LAMOST J024048.51+195226.9

Abstract: It was recently proposed that the cataclysmic variable (CV) LAMOST J024048.51+195226.9 may be a twin to the unique magnetic propeller system AE Aqr. If this is the case, two predictions are that it should display a short period white dwarf spin modulation, and that it should be a bright radio source. We obtained follow-up optical and radio observations of this CV, in order to see if this holds true. Our optical high-speed photometry does not reveal a white dwarf spin signal, but lacks the sensitivity to detect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
(50 reference statements)
3
5
0
Order By: Relevance
“…We unsuccessfully searched for a photometric signature of the spinning WD as is seen in AE Aqr. We placed a 4 mmag upper limit on the g-band spin amplitude for periods between 6.3 s and 85 s. This is consistent with the nondetection of a spin signal noted by Pretorius et al (2021).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We unsuccessfully searched for a photometric signature of the spinning WD as is seen in AE Aqr. We placed a 4 mmag upper limit on the g-band spin amplitude for periods between 6.3 s and 85 s. This is consistent with the nondetection of a spin signal noted by Pretorius et al (2021).…”
Section: Discussionsupporting
confidence: 81%
“…The propellers and AR Sco appear to efficiently extract spin energy from their WDs, and are unusually strong radio emitters, implying a significant nonthermal power source derived from an interaction with the rapidly spinning magnetic WD. (Bookbinder & Lamb 1987;Stanway et al 2018;Pretorius et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Two subsequent studies have added additional weight to the connection between J0240+1952 and AE Aqr. Pretorius et al (2021) detected radio emission, with a radio luminosity close to the highest measured of any CV, higher even than AE Aqr, while Garnavich et al (2021) found that the Balmer emission lines broadened up to ±3000 km/s during flares, and showed that a P Cygni-like component in H𝛼, also seen by Thorstensen (2020), was consistent with Wynn et al (1997)'s magnetic propeller model.…”
Section: Introductionsupporting
confidence: 68%
“…The flares are also seen spectroscopically in increased fluxes and widths of the Balmer lines (Reinsch & Beuermann 1994). Rounding off the list of notable properties, AE Aqr was one of the first CVs to be detected at radio frequencies (Bookbinder & Lamb 1987), and is one of the most luminous of all CVs in terms of radio power (Pretorius et al 2021). The radio flux is thought to be generated by synchrotron emission from expanding clouds of plasma (Meintjes & Venter 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation